Ice-nucleating ability of aerosol particles and possible sources at three coastal marine sites - M. Si; V. E. Irish; R. H. Mason; J. Vergara-Temprado; S. J. Hanna; L. A. Ladino; J. D. Yakobi-Hancock; C. L. Schiller; J. J. B. Wentzell; J. P. D. Abbatt; K. S. Carslaw; B. J. Murray; et al. (Atmospheric Chemistry and Physics, 2018)
Despite the importance of ice-nucleating particles (INPs) for climate and precipitation, our understanding of these particles is far from complete. Here, we investigated INPs at three coastal marine sites in Canada, two at mid-latitude (Amphitrite Point and Labrador Sea) and one in the Arctic (Lancaster Sound). For Amphitrite Point, 23 sets of samples were analyzed, and for Labrador Sea and Lancaster Sound, one set of samples was analyzed for each location. At all three sites, the ice-nucleating ability on a per number basis (expressed as the fraction of aerosol particles acting as an INP) was strongly dependent on the particle size. For example, at diameters of around 0.2 µm, approximately 1 in 10 6 particles acted as an INP at −25 °C, while at diameters of around 8 µm, approximately 1 in 10 particles acted as an INP at −25 °C. The ice-nucleating ability on a per surface-area basis (expressed as the surface active site density, n s ) was also dependent on the particle size, with larger particles being more efficient at nucleating ice. The n s values of supermicron particles at Amphitrite Point and Labrador Sea were larger than previously measured n s values of sea spray aerosols, suggesting that sea spray aerosols were not a major contributor to the supermicron INP population at these two sites. Consistent with this observation, a global model of INP concentrations under-predicted the INP concentrations when assuming only marine organics as INPs. On the other hand, assuming only K-feldspar as INPs, the same model was able to reproduce the measurements at a freezing temperature of −25 °C, but under-predicted INP concentrations at −15 °C, suggesting that the model is missing a source of INPs active at a freezing temperature of −15 °C.